Measurement, measures and the millennium - the Society's activities in a long perspective - Black, R. D. Collison (Statistical and Social Inquiry Society of Ireland, 1988)
"But the age of chivalry is gone. That of sophisters, economists and calculators has succeeded " (Edmund Burke, 1790). Nevertheless, the economists and calculators had begun their work well before the day when Burke made his comment. In recent times the old-established view that the origin of political economy as a scientific and independent discipline could be dated from the publication of Smith's 'Wealth of Nations' in 1776 has undergone considerable revision.
Read before the Society, 21 April 1988
Keywords: History of statistical analysis; 314.15